KEPASTIAN HUKUM DALAM PENERAPAN SISTEM PENDAFTARAN MEREK KONSTITUTIF PADA SENGKETA MEREK "CRYSTAL X" - Aditya Adjitama (2021)
The purpose of this study is to examine the legal certainty of a constitutive trademark registration system. Indonesia as an adherent of a constitutive trademark registration system by implementing the First to File principle, which means that a trademark is legally recognized and protected by law after a trademark is registered as the first. However, even though a trademark has been legally registered as the first one, in fact it can still be canceled upon a court decision on a third party lawsuit, such as in the case of the "Crystal X" mark. This study uses juridical normative legal research methods. The result of this study is the registration of CV's "Crytal-X" brand. Crystal X at DJKI for class 3 which is carried out in accordance with applicable regulations, with legal certainty that the brand must be protected and CV. Crystal X as the registered trademark owner owns the exclusive rights to the "Crystal-X" mark. However, as the first registrant in grade 3, the brand "Crystal-X" belongs to CV. Crystal X was sued by PT.Natural Nusantara who objected to the registration of CV's trademark. Crystal X. Through the judge's judgment, based on the facts, the trademark was CV. Crystal X was canceled on the argument that the CV. Crystal X was registered in bad faith